Phosphorylation of Msx1 promotes cell proliferation through the Fgf9/18-MAPK signaling pathway during embryonic limb development. Issue 20 (20th October 2020) - Yang, Yenan; Zhu, Xiaoli; Jia, Xiang; Hou, Wanwan; Zhou, Guoqiang; Ma, Zhangjing; Yu, Bin; Pi, Yan; Zhang, Xumin; Wang, Jingqiang; Wang, Gang
Abstract: Msh homeobox (Msx) is a subclass of homeobox transcriptional regulators that control cell lineage development, including the early stage of vertebrate limb development, although the underlying mechanisms are not clear. Here, we demonstrate that Msx1 promotes the proliferation of myoblasts and mesenchymal stem cells (MSCs) by enhancing mitogen-activated protein kinase (MAPK) signaling. Msx1 directly binds to and upregulates the expression of fibroblast growth factor 9 ( Fgf9 ) and Fgf18 . Accordingly, knockdown or antibody neutralization of Fgf9/18 inhibits Msx1-activated extracellular signal-regulated kinase 1/2 (Erk1/2) phosphorylation. Mechanistically, we determined that the phosphorylation of Msx1 at Ser136 is critical for enhancing Fgf9 and Fgf18 expression and cell proliferation, and cyclin-dependent kinase 1 (CDK1) is apparently responsible for Ser136 phosphorylation. Furthermore, mesenchymal deletion of Msx1 / 2 results in decreased Fgf9 and Fgf18 expression and Erk1/2 phosphorylation, which leads to serious defects in limb development in mice. Collectively, our findings established an important function of the Msx1-Fgf-MAPK signaling axis in promoting cell proliferation, thus providing a new mechanistic insight into limb development.